Prinsip Produksi Keripik Tempe Az-Zahra Desa Sumber Rahayu Kecamatan Rambang Kabupaten Muara Enim dalam Perspektif Ekonomi Islam - Puspa Utami; Rika Rahmadina Putri; Inten Sriana (Assyarikah: Journal of Islamic Economic Business, 2023)
Production is an activity that links virtuous values starting from the management of sources obtained by sharia, the production process, to production results. The benevolence carried out is intended to provide many benefits for all parties involved. The purpose of this research is to determine the application of the principle of production of Az-zahra tempe chips in Sumber Rahayu Village, Rambang District, Muara Enim Regency and to determine the application of the principle of production of Az-zahra tempe chips based on production principles in Islam. This research is a field research using qualitative research. Data collection methods used are observation, interviews and documentation. The analysis technique used is data reduction, data presentation and drawing conclusions. Test the validity of the data used is the triangulation technique. From the research results it was found that there are 5 principles of production . The principle of monotheism is to give time to rest five times to employees and apply honesty in doing business. The principle of humanity is to provide work motivation to employees and how the working hours are for employees. The principle of justice is to provide wages and bonuses to employees and to do justice in the scales. the principle of benevolence, namely producing chips in a halal way and providing leave to employees in one month. The principles of freedom and responsibility, namely being responsible in the event of damage to tempeh chips and production waste management, have been well implemented, however, the virtuous principles, namely the virtuous principle, namely providing training to employees, have not been properly implemented in the Az-Zahra tempe chips business.